Production of Pesticide-Free Vegetables in Mae Lan District, Pattani Province - Phetcharat, Phonsawan; Muangkaewngam, Arunee; Kaewtathip, Wilaiwan; Wetosot, Somthob; Bueraheng, Niranee (YRU Journal of Science and Technology, 2022)
Pesticide-free vegetables are in great demand due to the consumers aware of their health. Thus, this study aims to investigate the situations, problems and obstacles of pesticide-free vegetable production in Mae Lan district, Pattani province from 29 vegetable farmers. The data were collected from interview using a questionnaire and analyzed using descriptive statistic. The findings showed that most of the farmers produce pesticide-free vegetables as their supplement job with 1-2 family members for less than 5 years in planting area of less than 5 rai. Among 15 of economic and local vegetables, cucumber was the most popular. Both chemical and organic fertilizers were used for soil improvement and growth of vegetable. For pest control plant extracts and chemicals were applied, harvested at safety period and sold to the local consumers. The income obtained from this activity was less than 100,000 Baht a year. So far, the pesticide-free vegetable production had not certified and faced with 2 major problems, the production and marketing. Production problems were disease and insect pests, weeds, drought in dry season, flood in rainy season and lack of capital. Marketing problems were uncertain of market demand and low price. It is necessarily to develop the market policy in order to secure the quantity and price of the vegetables, as well as to improve the knowledge of the farmers on production management of the pesticide-free vegetables.